A phytometer study evaluating the effects of stream restoration on riparian vegetation. Issue 4 (28th August 2015) - Dietrich, Anna L.; Nilsson, Christer; Jansson, Roland
Abstract: Channelization of streams and rivers to facilitate timber floating has cut off riparian zones from the channel, covered them with coarse sediment and resulted in less flooding. Restoration measures aiming to counteract these impacts are expected to create a higher, more natural hydrological variability and enhance site quality for riparian plants. In a long‐term field experiment, we evaluated the effect of flooding regime on riparian plant performance by measuring survival and biomass increment of two transplanted phytometer species, a grass ( Molinia caerulea ) and a forb ( Filipendula ulmaria ). We also analysed the number and duration of flooding events in channelized and restored stream and river reaches with an indirect method using diurnal temperature oscillation. We found that flow duration was higher, with significantly more flood events at restored compared with channelized sites in medium‐sized and large watercourses, particularly during the summer months. Phytometer performance was better at restored sites, and it was positively correlated with duration and frequency of summer flooding, indicating that more but less intense floods after restoration improved site conditions for phytometer growth. This may not only result from an increased heterogeneity in channel morphology caused by the return of boulders but can probably also be attributed to a reduced current velocity at restored sites. Flood variables were more often correlated with other abiotic variables at restored than at channelized sites, which points to an increased land–water connectivity as a result of restoration. Copyright © 2015 John Wiley & Sons, Ltd.